Value of Optical Genome Mapping (OGM) for Diagnostics of Rare Diseases: A Family Case Report - Kovanda A; Miljanović O; Lovrečić L; Maver A; Hodžić A; Peterlin B (Balkan Journal of Medical Genetics)
Optical genome mapping (OGM) is a novel method enabling the detection of structural genomic variants. The method is based on the laser image acquisition of single, labeled, high-molecular-weight DNA molecules and can detect structural genomic variants such as translocations, inversions, insertions, deletions, duplications, and complex structural rearrangements. We aim to present our experience with OGM at the Clinical Institute of Genomic Medicine, University Medical Centre Ljubljana, Slovenia. Since its introduction in 2021, we have used OGM for the testing of facioscapulohumeral muscular dystrophy 1, characterization and resolution of variants identified by other technologies such as microarrays, exome and genome next-generation sequencing, karyotyping, as well as testing of rare disease patients in whom no genetic cause could be identified using these methods.